2012
DOI: 10.1039/c1dt11032b
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustive oxidation of a nickel dithiolate complex: some mechanistic insights en route to sulfate formation

Abstract: A study of the step-wise oxidation of a Ni(II) diaminodithiolate complex through the formation of sulfate, the ultimate sulfur oxygenate, is reported. Controlled oxygenations or peroxidations of a neutral, planar, tetracoordinate, low-spin Ni(II) complex of a N(2)S(2)-donor ligand, (N,N'-dimethyl-N-N'-bis(2-mecaptoethyl)-1,3-propanediaminato) nickel(ii) (1), led to a series of sulfur oxygenates that have been isolated and characterized by ESI-MS and single-crystal X-ray diffraction. A monosulfenate complex (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 100 publications
1
15
0
Order By: Relevance
“…Complexes 1 and 9 have been previously synthesized, and crystal structures reported. 95,97,98 All characterization data, including ESI-MS spectra and elemental microanalysis are consistent with the formulations and structures given for each complex (see SI #1). Selected bond lengths and angles for 1, 2, 9, and 10 are given in Table 1.…”
Section: A Synthesis and Characterizations Of The Nickel Complexessupporting
confidence: 64%
See 1 more Smart Citation
“…Complexes 1 and 9 have been previously synthesized, and crystal structures reported. 95,97,98 All characterization data, including ESI-MS spectra and elemental microanalysis are consistent with the formulations and structures given for each complex (see SI #1). Selected bond lengths and angles for 1, 2, 9, and 10 are given in Table 1.…”
Section: A Synthesis and Characterizations Of The Nickel Complexessupporting
confidence: 64%
“…Complex 1 97 and 9 98 have been previously studied by X-ray crystallography. Complex 2 (Figure 2) and 10 (Figure 3) are novel.…”
Section: A Synthesis and Characterizations Of The Nickel Complexesmentioning
confidence: 99%
“…The formation of sulfate ions was verified by the observation of a colorless precipitate after addition of an aqueous BaCl 2 solution, and thus, we concluded that Bi 3+ induces the formation of sulfate from thiosalicylic acid. Note that the oxidation of ( N , N ′‐dimethyl‐ N , N ′‐bis(2‐mercaptoethyl)‐1,3‐propanediaminato) nickel(II) gave [Ni(dmf) 5 (H 2 O)]SO 4 45. It is reported that the stepwise oxidation of the cis ‐dithiolate by hydrogen peroxide or oxygen in DMF produces a number of sulfur oxygenate nickel complexes.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the stepwise oxidation of the cis ‐dithiolate by hydrogen peroxide or oxygen in DMF produces a number of sulfur oxygenate nickel complexes. Starting from the cis ‐dithiolate, insertion of oxygen primarily leads to the sulfenate complex, subsequent oxidation gives the sulfinate followed by the sulfonate right up to the sulfate [Ni(dmf) 5 (H 2 O)]SO 4 45. In case of [Bi 2 (SO 4 ) 2 (dmso) 8 ](HSO 4 ) 2 ( 1 ) a similar formation process might be conceivable.…”
Section: Resultsmentioning
confidence: 99%
“…The isolation of intermediate dimer 9 demonstrated that peroxidations and oxygenations do not necessarily proceed from the monosulfinate to the disulfinate en route to the disulfonate complexes, and that the ultimate decomposition of the ligand leads to the formation of sulfate. 12 The rate of metal-thiolate oxygenation by hydrogen peroxide was measured for the model complex 10 of nickel-containing superoxide dismutase (NiSOD). Under typical synthetic conditions the reaction proceeds within seconds yielding S-oxygenate products but under physiological conditions half-life times extended to several hours making the S-oxygenation of NiSOD kinetically limited under such conditions.…”
Section: Introductionmentioning
confidence: 99%